The Religious Patterns of the Tablighi Jamaat in Indonesia - Aep Saepuloh; Nandang Koswara; Asep Dadan Wildan (HK-Publishing, 2022)
Abstract One of the promises of religion is happiness for its followers. The promise is translated according to their respective mindstreem. One of them is the Tablighi Jamaat. The Tablighi Jamaat claims to be a neutral community in terms of sects, mass organizations, and politics, but within the framework of ahl al-sunnah wa aljamâ'ah. They emphasize their religious activities in real terms through the practice of da'wah by prioritizing morality. This study aims to determine the religious pattern of the Tablighi Jamaat by studying the pattern of their life and da'wah. This study uses a qualitative approach with a descriptive method in describing the results of the study. The results of the research on the religious patterns of the Tablighi Jamaat mutually influence the dimensions of doctrine, teachings, rituals, appreciation and practice, so that the social interactions that are formed between the two are dialectically and associatively intertwined because they are influenced by motivational orientations and value orientations. In the application of the religious pattern, the Tablighi Jamaat adheres to the six doctrinal principles they profess. Keywords: Religion, Tablighi Jamaat, Religious Patterns.